Successful transcatheter mitral valve replacement in a patient with bioprosthetic valvular degeneration and severe regurgitation - Beytullah Çakal; Sinem Deniz Çakal; Oguz Karaca; Mehmet Onur Omaygenc; Aydın Yıldırım (KARE Publishing, 2019)
The implantation of aortic transcatheter heart valves has been successfully performed throughout the world in hundreds of patients with severe dysfunction of a degenerated mitral bioprosthesis or those at high surgical risk for re-operation. The transseptal approach may be more technically challenging, but is a less invasive procedure and may have a lower mortality rate compared with a transapical approach, and also offers a quick patient recovery. This report is a description of a rare case in Turkey: a successful transseptal mitral valve replacement in a case of a failed bioprosthetic valve. This case illustrates the feasibility and safety of percutaneous valve-in-valve implantation to treat a degenerated bioprosthesis.